Pelanggaran Notaris yang Bekerja sama Melalui Platform Media Sosial dengan Pihak Ketiga - Vivia Chandra; Tjhong Sendrawan (Dinasti Review Publisher, 2024)
Along with technological developments, social media is increasingly being used by almost all groups. Social media is a means for third parties to promote notarial deeds. The problem in this article is the legal and ethical violations committed by notaries who collaborate via social media platforms provided by third parties. The aim of the research is to analyze the legal and ethical rules regarding notaries who collaborate via social media platforms provided by third parties. This research was conducted because there is no clear and detailed law enforcement regarding notaries collaborating via social media platforms provided by third parties. This research method is doctrinal legal research with moral rules regulated based on the agreement of members of the Indonesian Notary Association organization. The research results of notaries working together through social media platforms provided by third parties, to promote the making of notarial deeds, is a violation of UUJN and the Code of Ethics. The violation committed by the notary was violating the provisions of Article 4 UUJN regarding the oath of office and the provisions of Article 4 paragraphs (3) and (4) of the Notary Code of Ethics regarding promotion and seeking clients. However, the notary's violations regarding promotion and seeking clients via social media were not explained in detail. Thus, the Indonesian Notary Association organization should update the Notary Code of Ethics to provide direction regarding the use of social media by notaries.